The right to life and fatal accidents at work in companies in productive sectors - Armas Morales, Carlos E. (2020)
This article deals with evaluating fatal accidents in work environments in groups of companies in various sectors of the economy with the aim of describing and understanding if the State regulations are assimilated by business management in the sense of complying with them to avoid fatal accidents that it involves loss of human life. This study is carried out under a qualitative approach, for which statistics from the Ministry of Labor and Employment Promotion, documents or accident reports in official and unofficial publications, observations, and expert interviews are used. The results conclude that the State regulations on safety at work have not penetrated the business behavior of the companies evaluated that fail to comply with the legal mandate, facilitating workplace accidents with the loss of workers' lives.